(untitled) (Lex localis - Journal of Local Self-Government, 2025)
This study constructs and confirms a Digital Brand Building Index (DBBI), among private universities in Telangana, India. The digital transformation has since become vital in the marketing of higher education and there is yet to be established a unified tool that can quantify the success of universities in their online brand building efforts. To define online brand-building comprehensively, this paper proposes seven dimensions that include Content Quality, Social Engagement, Electronic Word of Mouth (e WOM), Search Visibility, Website Experience, Paid Media Breadth and Online Reputation. Two large student samples were used to conduct the research on a multi-stage scale development basis. The underlying factor structure was defined using the Exploratory Factor Analysis (EFA) and the construct validity using the Confirmatory Factor Analysis (CFA). Final 24-item DBBI showed good reliability, convergent, and discriminant validity, and gender and program type measurement invariance. Nomological validity was determined by establishing positive correlation among DBBI, university brand equity and institutional reputation. DBBI is a practical benchmarking tool; it has percentile-based bands of managerial decision-making. Future empirical research associating DBBI with student enrollment outcomes has its foundation in this paper.